Blood glucose levels in hyperglycemic white rats administered various preparations of bay leaves - Zaenab, Siti; Nurwidodo, Nurwidodo (Universitas Wiralodra, 2025)
Elevated blood glucose levels, known as Hyperglycemia, are a key feature of diabetes mellitus (DM), which remains a primary global health challenge. The rising prevalence of type 2 diabetes and the side effects of synthetic drugs have led to interest in natural alternatives. Bay leaves (Syzygium polyanthum), commonly used in Indonesian cuisine, contain bioactive compounds such as flavonoids, tannins, and terpenoids that may have antidiabetic properties. This study examined the effect of bay leaves preparations—decoction, tea, and filtrate—on blood glucose levels in hyperglycemic white rats and identified the most effective form. A proper experimental design involved 25 male rats, divided into five groups: a negative control, a positive control (alloxan only), and three treatment groups (decoction, tea, and filtrate). Hyperglycemia was induced using alloxan (150 mg/kg BW), and treatments were given orally twice daily for 30 days. Blood glucose levels were measured before and after treatment using a GlucoDr glucometer. Data were analyzed using one-way ANOVA and the LSD test (α = 0.05). Significant differences were observed among groups (Fhit = 16.61 > Ftab = 2.87). The decoction group had the most considerable glucose reduction (112.4 mg/dL), closely followed by the negative control (118 mg/dL), while the tea and filtrate groups showed lesser effects. Decoction proved most effective, likely due to better compound extraction. These findings highlight the potential of bay leaves decoction as a natural remedy for hyperglycemia, warranting further clinical research.